Growth and Antioxidant-Related Effects of the Reestablished Ascorbic Acid Pathway in Zebrafish (Danio rerio) by Genomic Integration of L-Gulonolactone Oxidase From Cloudy Catshark (Scyliorhinus torazame) - Shanaka, K. A. S. N.; Jung, Sumi; Janson, N. D.; Jayasingha, J. R. P.; Madushani, K. P.; Kim, Myoung-Jin; Lee, Jehee (Frontiers in Physiology, 2021)
Loss of L-gulonolactone oxidase (GULO), which catalyzes the last step of ascorbic acid (AA) biosynthesis pathway, results in a complete lack of AA in several Osteichthyes fish species, including zebrafish. In this study, sGULO, the active GULO gene from cloudy catshark (Scyliorhinus torazame) was cloned into zebrafish using Gateway cloning method. The resulting Tg(-actin:sGULO:mCherry) fish were analyzed for the effects of a re-established AA pathway. Fluorescent microscopy and PCR were used to analyze the integration of the construct into zebrafish genome. Catalytic activity of sGULO, AA production, growth-related characteristics, and gene expression were investigated to evaluate the effects of AA production in Tg fish. The mCherry fluorescent protein indicated the proper integration and expression of the sGULO construct in zebrafish. The sGULO gene was ubiquitously expressed in all the studied tissues and the enzyme activity indicated an increased AA production in Tg fish. The growth of Tg fish was also increased, while antioxidant system analysis suggested that ROS production was reduced in Tg fish compared to wild type. Expression of the AA transporter slc23a1 was significantly downregulated in Tg homozygous fish. These results collectively indicate the effects of re-established AA synthesis in zebrafish.